2007
DOI: 10.1021/ie0702781
|View full text |Cite
|
Sign up to set email alerts
|

1,2,4-Trimethylbenzene Transformation Reaction Compared with its Transalkylation Reaction with Toluene over USY Zeolite Catalyst

Abstract: Abstract1,2,4-Trimethyl benzene (TMB) transalkylation with toluene has been studied over USY-zeolite type catalyst using a riser simulator that mimics the operation of a fluidized-bed reactor. 50:50 wt% reaction mixtures of TMB and toluene were used for the transalkylation reaction. The range of temperature investigated was 400-500 o C and time on stream ranging from 3 to 15 seconds.The effect of reaction conditions on the variation of p-xylene to o-xylene products ratio (P/O), distribution of trimethylbenzene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 20 publications
3
10
0
Order By: Relevance
“…Toluene is also an important component for transalkylation with trimethylbenzenes to provide xylenes. 1,2,4-Trimethylbenzene (TMB) transalkylation with toluene has been studied over USY zeolite type catalyst [22]. Reaction mixture of 50:50 wt% TMB and toluene was used.…”
Section: Introductionmentioning
confidence: 99%
“…Toluene is also an important component for transalkylation with trimethylbenzenes to provide xylenes. 1,2,4-Trimethylbenzene (TMB) transalkylation with toluene has been studied over USY zeolite type catalyst [22]. Reaction mixture of 50:50 wt% TMB and toluene was used.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] However, it was found that medium-pore zeolites, like ZSM-5, have a higher selectivity towards p-xylene. Firstly, the pores need to be large enough for the diffusion of the bulky TMB species.…”
Section: Introductionmentioning
confidence: 99%
“…This is conrmed by Krejčí and coworkers. 21 Al-Khattaf et al 22 reported that USY gave high xylene yield in the transalkylation of toluene with 1,2,4-TMB that was carried out in a riser simulator reactor. Lee et al 23 investigated the catalytic activity of zeolites with 12-MR in the transalkylation reaction and found that MOR zeolite showed high activity and stability, especially aer dealumination.Čejka et al 24 attributed the high catalytic activity of large-pore zeolites to accommodation of more reactants inside their channel systems, which led to an increase in the probability of occurrence of bimolecular reaction.…”
Section: Introductionmentioning
confidence: 99%